2017
DOI: 10.1021/acs.jproteome.6b00859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet Quality and Psychosocial Stress on the Metabolic Profiles of Mice

Abstract: There has been an increasing interest in relationship between stress and diet. To address this relationship, we evaluated an animal model of depression: male C57BL/6J mice subjected to subchronic mild social defeat stress (sCSDS) for 10 consecutive days using male ICR mice under two different calorie-adjusted diets conditions-nonpurified (MF) and semipurified (AIN) diets made from natural and chemical ingredients mainly, respectively. Our previous study indicates that diet quality and purity affect stress susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…Several experimental studies have previously shown how the profile of blood metabolites could reflect behavioural symptoms. In mice, stress has been indicated by higher plasma levels of 4-hydroxyproline, 3-aminopropanoic acid, orotic acid, and lower urea, dihydroxyacetone, ribose, lactic acid, and glycerol 14 . In dogs, behavioural scores similar to attention-deficit/hyperactivity disorder have been associated positively with kynurenic acid, fatty acids (20:4) and (18:1), and negatively with phospholipids and microbial metabolites of tryptophan such as indole acetic acid and 3-indolepropionic acid 15 .…”
mentioning
confidence: 99%
“…Several experimental studies have previously shown how the profile of blood metabolites could reflect behavioural symptoms. In mice, stress has been indicated by higher plasma levels of 4-hydroxyproline, 3-aminopropanoic acid, orotic acid, and lower urea, dihydroxyacetone, ribose, lactic acid, and glycerol 14 . In dogs, behavioural scores similar to attention-deficit/hyperactivity disorder have been associated positively with kynurenic acid, fatty acids (20:4) and (18:1), and negatively with phospholipids and microbial metabolites of tryptophan such as indole acetic acid and 3-indolepropionic acid 15 .…”
mentioning
confidence: 99%
“…The P values were adjusted using the Benjamini−Hochberg correction, and post-adjustment are referred to as Q values. The metabolome-wide significance threshold was set at Q < 0.1, following previous studies [26,27,50,51].…”
Section: Methodsmentioning
confidence: 99%
“…Typical metabolite analyses use gas chromatography–mass spectrometry (GC–MS), liquid chromatography–mass spectrometry (LC–MS), capillary electrophoresis–mass spectrometry (CE–MS), and nuclear magnetic resonance (NMR). Metabolome analyses have previously been used to identify changes caused by stress and/or feed in mice using CE–MS [26] and GC–MS [27], so we expect a metabolomics approach to provide useful insight into the role of breed and feed in determining egg composition.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma β-alanine levels were shown to be increased in models of rodents with depression [136] and intracerebroventricular administration of this amino acid that inhibited exploratory behaviour and motility in chicks [137]. In contrast, a diet supplemented with β-alanine induced anxiolytic-like behaviour in mice under acute stressful conditions with concomitant reductions in 5-hydroxyindoleacetic acid (a major metabolite of serotonin) in the hippocampus [138].…”
Section: Animal Studies Of the Role Of Carnosine In Brain-related mentioning
confidence: 99%